La Drépanocytose Chez Les Enfants Hospitaliers Au Service De Pédiatrie (CHR El Idriss De Kénitra, Maroc): A Propos De 53 Cas. - A., Belala; I., Marc; A., Hajji.; D., Belghyti.; K., El kharrim. (European Scientific Journal, ESJ, 2016)
The objective of this work is to study sickle cell in children 1 to 16 years at El Idrissi regional hospital of Kenitra (Morocco) The study was conducted between March and June 2012. The population includes 53 patients, 39 male and 14 female. The studied parameters were age, sex, socioeconomic status, origin, age of diagnosis and schooling. Data on sickle cell patients was collected from information sheets available from the archives department at the El Idrissi regional hospital of Kenitra and a patient’s verbal consent or that of the child’s parents. Sickle cell disease is the third leading cause of admission (10.16 % of total admissions). 47.16 % of patients are under the age of 6 years. The diagnosis of disease is made in 32.07 % of the cases around 9 months. In 94.3% of cases, patients are from family whose father has a low and irregular income. The main causes of hospitalization are painful crises (69.81 %), acute anemia (28.30%), and infections (28.30%). As a medical treatment, the rehydration, analgesics, antibiotics and blood transfusions are the most prescribed. The transfusion was performed in 96.22 % of cases. The lack of early detection and socio –economic pressures and environmental conditions seems to put our patients in a vulnerable state.The focus should be on prevention and strengthening the capacity of families.